Large Eddy Simulation of flow past three elliptical cross-section cylinder arrays in equilateral triangle arrangement - et. al, Rajesh Kumar (International Journal of Advanced Science and Technology, 2019)
The stream past different bluff bodies in array has been the chief area of interest to carry out research for many analysers for the past spans of years. To judge the flow characteristics throughout assemblage of cylinders, numerical simulation of flow over three elliptic cylinders in an equilateral triangle arrangement for two Reynolds numbers i.e. 10200 and 15200 across the elliptic cylinders is examined in this paper. Simulation is performed by choosing 3-D LES (Large-eddy simulation) executed with the help of commercial software ANSYS Fluent 19R1. The simulation results consist of both qualitative and quantitative findings with velocity vectors contours of flow for both the Reynolds numbers, lift and drag coefficients, and Power spectral density plots.